Molecular markers for species identification of Hessian fly males caught on sticky pheromone traps - Chen, Ming-Shun; Wheeler, Shanda; Davis, Holly; Whitworth, R. Jeffery; Knutson, Allen; Giles, Kristopher L.; Royer, Tom A.; Skinner, Margaret (My University, 2014)
Pheromone traps have been widely used to monitor insect population activity. However, sticky pheromone traps for the Hessian fly (Mayetiola destructor), one of the most destructive pests of wheat, have been used only in recent years. Hessian fly male adults are small and fragile, and preserving specimens during sorting of sticky pheromone traps is a challenge when intact specimens are often required to visually distinguish them from related insects such as fungus gnats. In this study, we have established a quick and reliable method based on polymerase chain reaction markers to correctly distinguish Hessian fly males from other closely related insects. Two Hessian fly-specific markers were established, one based on the trypsin gene MDP-10 and the other based on a gene encoding the salivary gland protein SSGP31‐5. Both markers provided >98% identification success of 110 Hessian fly samples prepared from single insects. The method should provide a useful tool to allow for identification of Hessian fly individuals on sticky pheromone traps or in other situations when Hessian fly eggs, larvae, pupae, and adults are difficult to distinguish from other insects.
Citation: Chen, M., . . . & Skinner, M. (2014). Molecular Markers for Species Identification of Hessian Fly Males Caught on Sticky Pheromone Traps. Journal of Economic Entomology, 107(3), 1110-1117. https://doi.org/https://doi.org/10.1603/EC13384
Keywords: Mayetiola destructor; Hessian fly; Pheromone trap; Wheat; Molecular marker